Simultaneously Influence of Magnetic and Electrical Field on the Human Body - Dimitrov, D. Tz. (Elektronika ir Elektrotechnika, 2008)
An investigation on influence of magnetic field on the trajectory of movement of ions in alive tissues in the case of electrotherapy by application of apparatus AMLIPULS is described in the paper. An mathematical description of movement of ions in alive tissues is done on the base of space disposition of vectors of electrical intensity and magnetic induction. Then some results of computer simulation of movement of ions of Na is described in the paper as these ions and ions of Cl  have the main level in the blood in the case of simultaneously influence of low frequency electrical signals with amplitude modulation and permanent magnetic field. Ill. 5, bibl. 8 (in English; summaries in English, Russian and Lithuanian).